HUMAN RESOURCE DIGITAL COMPETENCE AS A KEY TO INNOVATION AND COMPETITIVE ADVANTAGE IN CREATIVE ECONOMY SMES - Setyo Gunawan; Muhammad Faisal; Nur Hidayat (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study investigates the role of human resource digital competence in enhancing product innovation and fostering competitive advantage among SMEs operating in the creative economy sector in Indonesia. A quantitative research design was employed using a survey method. Data were collected from 500 respondents consisting of SME owners and employees in the creative economy subsector in Pontianak and surrounding areas. Structural Equation Modeling (SEM) with WarpPLS 8.0 was used to test the hypothesized relationships between digital competence, product innovation, and competitive advantage. The measurement model was assessed for validity and reliability, while the structural model was evaluated using path coefficients, coefficient of determination, and predictive relevance indices. The findings reveal that human resource digital competence has a significant positive influence on product innovation (β = 0.805, p < 0.001) and competitive advantage (β = 0.368, p < 0.001). Furthermore, product innovation significantly affects competitive advantage (β = 0.472, p < 0.001) and mediates the relationship between digital competence and competitive advantage (p < 0.001). The model demonstrates strong explanatory power with R² values of 0.647 for product innovation and 0.650 for competitive advantage. The findings provide actionable insights for SME managers to enhance digital competence through targeted training and development programs, for policymakers to design integrated digital literacy and innovation support initiatives, and for business support organizations to tailor their services to address the specific needs of creative economy SMEs.